An Analysis of Micro Enterprise Developrnent Factors in Dealing Business Cornpetition in Medan City - Siti Mujiantun, S.E., M.M. (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA)
An Analysis of Micro Enterprise Developrnent Factors in Dealing Business Cornpetition in Medan City